Pemanfaatan Open-Source Intelligence untuk Deteksi dan Penanganan Cybercrime Judi Online Berbasis Forensik Digital - Ramdani, Maullidan Alfa Rizki Fikri; Hadiana, Asep Id; Ilyas, Ridwan (Jurnal Algoritma, 2025)
The phenomenon of cybercrime related to online gambling is increasing in Indonesia, with web defacement attacks and backdoor insertion on websites that damage the psychological aspects of players and the family economy. This research aims to identify and analyze the threats posed by online gambling through Open-Source Intelligence (OSINT) and penetration testing methods. Using the Google Dorking technique, OSINT successfully identified sites involved in online gambling, while penetration testing uncovered system weaknesses that perpetrators exploit, such as SQL Injection and Cross-Site Scripting (XSS), which allow backdoor insertion. The results of this study demonstrate the effectiveness of OSINT and penetration testing in identifying sites that are vulnerable to attacks as well as loopholes that are often exploited by perpetrators. In addition, this research highlights the importance of digital forensics in handling legitimate electronic evidence for the court. As a scientific contribution, this research proposes the development of more accurate backdoor detection tools, the improvement of web security systems, as well as the implementation of rapid response in dealing with online gambling threats. This research is expected to assist the government and society in addressing cybercrime threats in Indonesia and strengthen policies and strategies to protect digital infrastructure.